1991
DOI: 10.1523/jneurosci.11-01-00210.1991
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and immunocytochemical compartments of the thalamic VPM nucleus in monkeys and their relationship to the representational map

Abstract: The ventral posteromedial nucleus (VPM) of the monkey thalamus was investigated with correlative anatomical and physiological techniques. On the basis of staining for cytochrome oxidase (CO), VPM is divided into a lightly stained, background matrix domain and an intensely stained rod domain. The latter consists of elongated rods of large, medium, and small cells, 500 microns wide on average and extending anteroposteriorly, many of them through the full extent of the nucleus. The matrix, consisting of small cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
68
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(78 citation statements)
references
References 22 publications
8
68
0
2
Order By: Relevance
“…Thus, the small cells in VP are not targets of the lemniscal path (11,12), and the small cell layers of GL in galago (layers 4 and 5) receive small fibers from the superior colliculus (SC), which, in turn, is the target of the smallest fibers of the optic tract (3,13). The general principle we seek may simply be that pathways to the superficial layers Abbreviations: GL, lateral geniculate nucleus; Lat, lateral nuclear group; Po, posterior nuclear group; Pul, pulvinar nucleus; SC, superior colliculus; VP, ventral posterior nucleus; VPi, inferior division of the VP; VPs, superior division of the VP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the small cells in VP are not targets of the lemniscal path (11,12), and the small cell layers of GL in galago (layers 4 and 5) receive small fibers from the superior colliculus (SC), which, in turn, is the target of the smallest fibers of the optic tract (3,13). The general principle we seek may simply be that pathways to the superficial layers Abbreviations: GL, lateral geniculate nucleus; Lat, lateral nuclear group; Po, posterior nuclear group; Pul, pulvinar nucleus; SC, superior colliculus; VP, ventral posterior nucleus; VPi, inferior division of the VP; VPs, superior division of the VP.…”
mentioning
confidence: 99%
“…In the past few years, Jones and his colleagues (11,12,14) have shown that large and small cells in the thalamus differ in their staining for calcium binding proteins, calbindin and parvalbumin. The clusters of big cells in VP of the monkey are rich in parvalbumin, whereas the small, pale cells in the matrix are rich in calbindin.…”
mentioning
confidence: 99%
“…sensory information from the moving ear. The VL, which showed c-Fos-IR in gerbil #2, is reported to have some connection with the SI, at least in the primate [18], and might also be activated by cells in the SI. The connection between the BMI-application area of the SI and DLG is not known.…”
Section: Discussionmentioning
confidence: 98%
“…In healthy animals, neural elements of the lemniscal somatosensory pathway from the spinal cord (e.g., spinocervical tract; Willis and Coggeshall 2004) to the brain stem (e.g., dorsal column nuclei) and thalamus have different staining properties from those of the spinothalamic pathway. Elements in the lemniscal pathway immunostain for the calcium-binding protein parvalbumin, whereas those in the spinothalamic pathway stain for 28-kDa calbindin (Rausell and Jones 1991b;Rausell et al 1991Rausell et al , 1992a.…”
Section: Injury Dependent Plasticity: Summarymentioning
confidence: 99%
“…For example, a skin locus such as the tip of a single finger has been stimulated at different frequencies while a monkey carries out a frequency discrimination task (Recanzone et al 1992). This task produced changes in the representation of the hand in S1 cortex, whereas a similar result was found in human S1 cortex, as mapped by high-resolution electroencephalography (Braun et al 2000).…”
Section: Activity-dependent Plasticity: Summarymentioning
confidence: 99%